2008
DOI: 10.1016/j.pbb.2008.03.006
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptors and alcohol

Abstract: There is substantial evidence that GABAergic neurotransmission is important for many behavioral actions of ethanol and there are reports spanning more than 30 years of literature showing that low to moderate (3-30 mM) concentrations of ethanol enhance GABAergic neurotransmission. A key question is which GABA receptor subunits are sensitive to low concentrations of ethanol in vivo and in vitro. Recent evidence points to a role for extrasynaptic receptors. Another question is which behavioral actions of alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
129
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(130 citation statements)
references
References 62 publications
0
129
0
1
Order By: Relevance
“…addiction | reward | self-administration | tonic inhibition G ABA A receptors (GABA A Rs) have long been considered a primary target for alcohol actions, including the voluntary consumption of alcohol (1)(2)(3)(4)(5). For example, treatment with the GABA A agonist 4,5,6,7-tetrahydroisoxazolo [5,4-c]pyridin-3-ol (THIP) enhances the acquisition of alcohol consumption in laboratory rats (6), whereas the opposite effect, a reduction of alcohol self-administration, is observed after administration of the GABA A R antagonists Ro15-4513 or picrotoxin (7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…addiction | reward | self-administration | tonic inhibition G ABA A receptors (GABA A Rs) have long been considered a primary target for alcohol actions, including the voluntary consumption of alcohol (1)(2)(3)(4)(5). For example, treatment with the GABA A agonist 4,5,6,7-tetrahydroisoxazolo [5,4-c]pyridin-3-ol (THIP) enhances the acquisition of alcohol consumption in laboratory rats (6), whereas the opposite effect, a reduction of alcohol self-administration, is observed after administration of the GABA A R antagonists Ro15-4513 or picrotoxin (7)(8)(9).…”
mentioning
confidence: 99%
“…δ mRNA and protein would be decreased at this time because our previous studies indicated that effects induced by this adenovirus on other genes [α 4 -subunit (32); BDNF (37)] are transient, with an effective time window of <2 wk, beginning around day 10 for both mRNA and behavioral changes. Notably, in our prior studies, peak behavioral changes have occurred ∼17-18 d after virus infusion (32,37).…”
mentioning
confidence: 99%
“…During the last decades it became clear that ethanol directly acts on proteins such as receptors and ion channels located in the plasma membrane or at intracellular signalling molecules. Experimental evidence revealed that some effects of ethanol are due to specific actions including most ligand-gated ion channels, such as glutamate-, -aminobutyric acid-(GABA) (Lobo & Harris 2008), dopamine-(Di Chiara & Imperato 1986), 5-hydroxytryptamine-, or acetylcholine-, opioid-, (Di Chiara et al 1996;Herz 1997;Gianoulakis 2009), adenosine-, ATP-(Asatryan et al, 2011Ostrovskaya et al, 2011), or TRP receptors (Benedikt et al, 2007, as well as voltage-gated ion channels, such as K + , Na + , and in particular Ca 2+ channels (Gonzales & Hoffman 1991;Crews et al, 1996b;Dopico et al 1996;Jakab et al 1997;Horishita & Harris 2008;Dopico & Lovinger 2009;Kerschbaum & Hermann 1997). Ethanol was also found to interact with signal-transduction mechanisms including Gproteins and protein kinases (Messing et al 1991;Lahnsteiner & Hermann 1995;Newton & Ron 2007;Martin 2010;Kelm et al 2011).…”
Section: Bk Channels -And Ethanol/acetaldehydementioning
confidence: 99%
“…Many of these subunit combinations have been examined for function and pharmacology in heterologous expression systems. To briefly summarize a large body of data, there is evidence that EtOH potentiates the function of α/β/γ-subunit-containing receptors, as well as those containing α4 or α6 along with β and δ subunits Lobo and Harris 2008;Mihic and Harris 1995;McCool et al 2003). However, none of these findings has been uniformly replicated in all laboratories that have examined EtOH effects in heterologous systems (reviewed in Lovinger and Homanics 2007;Aguayo et al 2002).…”
Section: Ligand-gated Ion Channels and Postsynaptic Ethanol Effectsmentioning
confidence: 99%